HADIS TENTANG MEMBUNUH ORANG MURTAD DALAM PERSFEKTIF FIKIH DAN MAKNA HADIS - ade pahrudin (Prodi Ahwal Al-Syakhsiyyah STAI Imam Syafi'i Cianjur, 2022)
The issue of the death penalty for apostates has received special attention from the western world of thought. Westerners regard it as ambiguous in accordance with Human Rights (HAM) in embracing their religion according to their own will. According to Fuqāhā, basically, there are two kinds of riddah; Riddah Mughāllaḍah is apostasy which is accompanied by acts of being hostile to Islam and influencing other Muslims to become apostates. While riddah mukhaffafah is simply apostasy without being accompanied by actions that depict hostility towards Islam. Although both forms of apostasy can be sentenced to death, in practice there are differences. This study aims to uncover and analyze the hadith that punishes the execution of apostates. This hadith invites debate because it seems contrary to the religious principles ordered by the Qur'an. The text of the Qur'an frees anyone to choose a religion, but there are a number of hadiths that say the execution of people who migrated from Islam.